## Các bạn giúp mik giải hai bài này vs nhé

Question

Các bạn giúp mik giải hai bài này vs nhé

in progress 0
4 years 2020-11-13T21:30:30+00:00 2 Answers 85 views 0

1. Giải thích các bước giải:

1a,(2x-3)^2+(4x-5)(x-7)

=4x^2-12x+9+4x^2-33x+35

=8x^2-45x+44

b,(x-2)(x+1)(x+2)-(x-1)^3

=x^3+x^2-4x-4-x^3+3x^2-3x+1

=4x^2-7x-3

c,(2x+5)(5-2x)+(3x-7)(x+2)

=-4x^2+25+3x^2-x-14

=-x^2-x+11

d,(2x+4)^2-(3x-5)^2

=4x^2+16x+10-9x^2+30x-25

=-5x^2+46x-15

2a,(2x-3)(x+1)-2(x-1)^2=3

<=>2x^2+2x-3x-3-2x^2+4x-2=3

<=>3x-5=3

<=>x=8/3

b,(4x+5)(2x-1)-(x+2)^2=(x-3)(x+3)

<=>8x^2-4x+10x-5-x^2-4x-4=x^2-9

<=>7x^2+2x=x^2

<=>6x^2+2x=0

<=>2x(3x+1)=0

<=>x=0 hoặc x=-1/3

c,(x-2)^2+(x+3)^2=(x+1)^2+15

<=>2x^2+2x+13=x^2+2x+1+15

<=>x^2-16+13=0

<=>x^2=3

<=>x= +-$\sqrt[]{3}$

Vậy …………………

2. 1a,(2x-3)^2+(4x-5)(x-7)

=4x^2-12x+9+4x^2-33x+35

=8x^2-45x+44

b,(x-2)(x+1)(x+2)-(x-1)^3

=x^3+x^2-4x-4-x^3+3x^2-3x+1

=4x^2-7x-3

c,(2x+5)(5-2x)+(3x-7)(x+2)

=-4x^2+25+3x^2-x-14

=-x^2-x+11

d,(2x+4)^2-(3x-5)^2

=4x^2+16x+10-9x^2+30x-25

=-5x^2+46x-15

2a,(2x-3)(x+1)-2(x-1)^2=3

<=>2x^2+2x-3x-3-2x^2+4x-2=3

<=>3x-5=3

<=>3x=8

<=>x=8/3

Vậy x=8/3

b,(4x+5)(2x-1)-(x+2)^2=(x-3)(x+3)

<=>8x^2-4x+10x-5-x^2-4x-4=x^2-9

<=>7x^2+2x=x^2

<=>6x^2+2x=0

<=>2x(3x+1)=0

<=>x=0 hoặc x=-1/3

Vậy S={0;-1/3}

c,(x-2)^2+(x+3)^2=(x+1)^2+15

<=>2x^2+2x+13=x^2+2x+1+15

<=>x^2-16+13=0

<=>x^2=3

<=>x= +-$\sqrt[]{3}$

Vậy x=+- $\sqrt[]{3}$